Exergaming for people with major neurocognitive disorder: a qualitative study. Issue 10 (8th May 2022) - Swinnen, Nathalie; Vandenbulcke, Mathieu; de Bruin, Eling D.; Akkerman, Riekje; Stubbs, Brendon; Vancampfort, Davy
Abstract: Purpose: This study investigated the experiences of participation in a standing balance exergame program amongst people with major neurocognitive disorder (MNCD) within residential care settings. Materials and methods: A qualitative descriptive study was conducted in participants with MNCD recruited from two residential settings. Participants exergamed for 15 min, three times per week for 8 weeks. Semi-structured interviews were conducted in all participants of the trial after 4 and 8 weeks. Audio files were transcribed and subsequently a thematic content analysis was performed using NVivo 12. Activity logs including adherence and attrition rates were kept. Results: Thirty-one participants with MNCD participated (median age = 85 (67–93) years; 77.4% women; Mini-Mental State Examination score = 19 (10–25)). Four broad themes emerged: (1) cognitive effects; (2) physical effects; (3) psychosocial effects and (4) motivators. The tailored exergame program was perceived as enjoyable. It stimulated participants' attention, concentration, reaction time, and memory. Participants reported improvements in balance, flexibility, and gait. Exergaming made participants energetic and calm. The attrition rate was 0% and the mean attendance rate was 79.3%. Conclusions: The results indicate that standing balance exergaming is feasible, beneficial, and engaging in people with MNCD. Implications for rehabilitation: Exergames present a personalised intervention for engaging people with major neurocognitive disorder in physical activity. An exergame intervention is feasible and highly appreciated in this population. Exergames should be adapted to the individuals' needs and possibilities in order to enhance motivation and learning.